International Regulations on Laundering and Repatriation of Illicit Funds: The Need for Reforms - ABUBAKAR, Samira (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2021)
The international community has been embattled with curbing corruption especially the one involving the embezzlement and looting of public treasuries in developing countries. One of the proactive steps taken includes regulations to prevent the laundering of such illicit funds and facilitating repatriation of such funds to the Victim’s Countries. However, in spite of such efforts, the aims of the regulations appear not to be far-reaching. Reports by international organisations such as the World Bank, Organisation for Economic Cooperation and Development (OECD) and Transparency International (TI) are used as yardsticks to measure adequacy of the existing international legal and institutional frameworks regulating the laundering and repatriation of illicit funds with emphasis on developing countries in Africa. This paper finds that efficient prevention of laundering and repatriation of illicit funds is contingent upon a functional system of international prosecution and asset recovery mechanism which includes diligent implementation of existing legal framework and adoption of new repressive measures such as an international adjudicatory mechanism. Therefore, it is recommended that the existing operative regulations should be fully deployed and efforts should be made by the international community towards establishing a new international adjudicatory mechanism that will prosecute offenders and facilitate prompt repatriation of illicit funds.